Evaluation of Motorcycle Energy Consumption in Urban Traffic - Pance, Stepan; Piskac, Daniel; Bures, Adam; Voldrich, Antonin; Kovac, Maros; Budiman, Bentang (http://dx.doi.org/10.31427/IJSTT.2019.2.1.4, 2019)
This paper aims to evaluate the energy consumption of motorcycle operating in urban traffic. Position, speed, and elevation in each time segment are collected by GPS - tracking data from the journey of motorcycle Honda Verza 150 in Bandung city. The distance, acceleration, and required tractive force for the motorcycle motion are then calculated. Furthermore, the energy consumption is investigated by modeling the motorcycle and calculating tractive force from the force equilibrium. For each time segment, engaged gear is then proposed for the best energy efficiency. The relationship among speed, required tractive force, and shifted gear according to time and distance are comprehensively discussed.